2008
DOI: 10.1016/j.physletb.2008.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Instantaneous interaction in massive gravity

Abstract: In general relativity, the instantaneous contributions to the gravitational potentials cancel each other in observable, leaving the theory free of physical instantaneous interactions. In models where these subtle cancellations are spoiled by the presence of fields that break Lorentz invariance, physical instantaneous interactions are possible. Such interactions are studied for a model of Lorentz-violating massive gravity.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2009
2009
2011
2011

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…Note, however, that the instantaneous part of the signal builds up gradually starting from zero at t = 0 and the maximum amplitude that is reached by the time t = |x|/c χ decreases with the distance as 1/|x| 2 . This is similar to the situation in Lorentz violating massive electrodynamics [28,29] and massive gravity [24,30]. It is worth stressing that due to the existence of a preferred frame the instantaneous propagation of signals does not lead to any inconsistencies.…”
Section: The Khronometric Model and Instantaneous Modessupporting
confidence: 71%
See 1 more Smart Citation
“…Note, however, that the instantaneous part of the signal builds up gradually starting from zero at t = 0 and the maximum amplitude that is reached by the time t = |x|/c χ decreases with the distance as 1/|x| 2 . This is similar to the situation in Lorentz violating massive electrodynamics [28,29] and massive gravity [24,30]. It is worth stressing that due to the existence of a preferred frame the instantaneous propagation of signals does not lead to any inconsistencies.…”
Section: The Khronometric Model and Instantaneous Modessupporting
confidence: 71%
“…12 Another derivation of the equivalence between (24) and (30) in the spherically symmetric case, which is also applicable for non-static configuration, is presented in [11]. However, it is based on the assumption that all leaves of the constant khronon field that foliate the space-time are regular and simply connected.…”
Section: Solutionsmentioning
confidence: 99%
“…Models described by the action (2.1) with the function F = F Z ij have been studied more intensively [18,21,30]. In particular, it has been shown that for −1 < γ < 0 and for γ = 1 the cosmological perturbations in these models behave identically to those in GR [21].…”
Section: The Massive Gravity Modelmentioning
confidence: 99%
“…This factor may cancel out in some special cases when the sources contain sufficient number of spatial derivatives, but not in general. Appearance of instantaneous interactions is a common feature of modified gravity models (more generally, gauge theories) with broken Lorentz invariance [20,[54][55][56]. In a theory that does not aspire to a Lorentz invariant UV completion this does not pose an obvious obstruction.…”
Section: Velocity-dependent Forces and Instantaneous Interactionmentioning
confidence: 99%